Genetic counseling for fetal gastrointestinal anomalies. Issue 2 (April 2020) - Schindewolf, Erica; Moldenhauer, Julie S.
Abstract : Purpose of review: Congenital gastrointestinal anomalies are common findings with relatively established methods of treatment. However, the genetic cause of how these defects occur and how that may impact a child's lifelong care is less established. Genetic testing has improved significantly in recent years, yet reviews documenting prenatal genetic counseling and testing guidelines have not been comprehensively updated. Recent findings: Congenital anomalies of the foregut, such as tracheoesophageal fistula carry a high association with genetic disorders, both in isolation and syndromic forms. Duodenal atresia remains highly associated with Trisomy 21 but is not enriched in other genetic conditions. Disorders of the midgut, such as omphalocele often have a genetic cause and may require both cytogenetic and panel testing to obtain a diagnosis. The etiologic basis of hindgut malformations remain largely unknown, though imperforate anus as well as Hirschprung's disease have been associated with many micro deletion syndromes as well as in association with other birth defects as part of larger syndromes. Summary: Prenatal diagnostic genetic testing through amniocentesis or chorionic villus sampling can be offered to every patient who wants to learn genetic information about their fetus. Cytogenetic testing, such as microarray is a first tier test to assess cause for these conditions and can provide meaningful answers. When a gastrointestinal anomaly is identified in association with an additionally affected organ system next-generation sequencing and defect-specific genetic testing panels can be necessary to understand cause as well as prognosis to best prepare families for the medical management that lies ahead.